Pengembangan Aplikasi Web Pelacakan Harga Situs Web E-commerce - Muhammad Fandy Fahreza Ramadhana Fauzi; Satrio Agung Wicaksono; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In 2017, five e-commerce sites in Indonesia with the highest number of unique visitors experienced an average growth of 97 percent. With this significant growth, new e-commerce companies must use various methods in order to compete in this industry. However, there are e-commerce that use unfavorable methods, for example using the